Organizational Controls and Performance Outcomes: A Meta‐Analytic Assessment and Extension - Sihag, Vikrant; Rijsdijk, Serge A. (Journal of Management Studies, 2019)
AbstractManaging employees and external partners effectively has been a primary concern for organizations and their managers. Many studies have investigated the effectiveness of organizational controls in a wide variety of contexts. Using organizational controls literature that discriminates amongoutcome, behaviour, and clan control, this study synthesizes the research on the effectiveness of these controls. In particular, the study examines 23,839 organizational controls–performance relationships from 120 independent samples, and tests several new hypotheses using advanced meta‐analytic methods. The results indicate that outcome, behaviour, and clan controls generally enhance performance, with each control having a distinct performance effect. Our analysis also demonstrates that controls function as complements to one another. This finding indicates that one form of control increases the effectiveness of other forms of control. We also examine the organizational controls–performance relationships across various contexts, and our results show that they vary according to the type of task. The paper concludes with a discussion on the theoretical and managerial implications of these findings.